1989
DOI: 10.1203/00006450-198904000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Natriuretic Factor During the Perinatal Period: Equal Depletion in Both Atria'

Abstract: ABSTRACT. Data in the literature concerning atrial natriuretic factor (ANF) physiology in the fetus and newborn, although limited, suggest significant activity during the perinatal period. To characterize further ANF physiology during this time, we documented immunoreactive ANF (IR-ANF) concentrations in the right and left atria before and immediately after birth a s well as in the hearts of immature and adult rats. There was a significant decrease in the concentration of IR-ANF in both right and left atria on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…This suggests diminishing basal (nonstimulated) ir-ANF release in the first few days after birth which correlates well with the observations of Dolan et al [1].…”
Section: Ir-anf Releasesupporting
confidence: 80%
See 2 more Smart Citations
“…This suggests diminishing basal (nonstimulated) ir-ANF release in the first few days after birth which correlates well with the observations of Dolan et al [1].…”
Section: Ir-anf Releasesupporting
confidence: 80%
“…This is consistent with diminishing ventricular ANF produc tion with progressive maturation, as has been previously observed in rats [20,21] and hu mans [22], However, the inability of this study to discriminate between ventricular and atrial ANF release to the perfusate prevents drawing such a conclusion with certainty. Alternatively, these data might represent readjustment in the balance of atrial ANF production and secretion, as suggested by the observation of Dolan et al [ 1], They reported biphasic change in ANF content of rat atria during the First 2 weeks after birth; ANF con tent declined during the first two days then increased to an apparent maximum by 15 days postpartum. Although comparison be tween rats and pigs carries some risk, our data suggest that decreasing basal (nonstimulated) ANF release during the First few days postpar tum could represent a resetting of a steadystate between ANF synthesis/storage and re lease.…”
Section: Ir-anf Releasementioning
confidence: 93%
See 1 more Smart Citation
“…Dolan et al (26) reported significantly higher atrial ANP content in 15-d-old preweaned rat pups compared with adult rats. Inscho et al (27) also found a greater atrial ANP content in 15-d-old preweaned rats than in postweaned or adult rats (when ANP content was factored for protein content).…”
Section: Resultsmentioning
confidence: 99%